Chikungunya virus populations experience diversity- dependent attenuation and purifying intra-vector selection in Californian Aedes aegypti mosquitoes - Riemersma, Kasen K.; Coffey, Lark L. (PLOS Neglected Tropical Diseases, 2019)
Author summary Chikungunya virus (CHIKV) is transmitted by Aedes aegypti mosquitoes and has caused explosive epidemics in Asia and the Americas since 2004. During mosquito infection, the CHIKV genome replicates with a high mutation rate to produce virus populations with high genetic diversity that facilitate virus evolution. With this study, we address three gaps in knowledge: 1) are Ae. aegypti mosquitoes from Los Angeles, California, capable of transmitting CHIKV, 2) what effect does increased CHIKV population diversity have on virus infection and transmission by mosquitoes, and 3) are there constraints to CHIKV evolution in mosquitoes? We use oral infection of Ae. aegypti mosquitoes originating from Los Angeles, California to demonstrate high laboratory transmission competence of CHIKV. We also show that oral infection of mosquitoes with CHIKV variants that produce more diverse populations are less able to infect mosquitoes than wildtype CHIKV populations. Lastly, our study provides evidence of genome-wide and regional constraints to CHIKV evolution within Ae. aegypti mosquitoes. Our results will inform public health risk assessments for potential CHIKV introduction in southern California and advance our understanding of the role of mosquitoes in CHIKV evolution.